FRI0407 Macrovascular involvement in systemic sclerosis patients: is there a relationship with microvascular peripheral blood flow?. (15th June 2017) - Paolino, S; Colombo, BM; Ruaro, B; Gotelli, E; Sulli, A; Ghio, M; Pizzorni, C; Alessandri, E; Patanè, M; Cutolo, M
Abstract : Background: Raynaud's phenomenon and digital ulcers are common clinical skin manifestations of the microvascular dysfunction in systemic sclerosis (SSc). Although microvascular and macrovascular abnormalities frequently coexist in disease such as diabetes mellitus and other vascular diseases, the possible association between microvascular failure and macrovasculopathy in SSc patients has not been deeply investigated (1). Objectives: The aim of the study was to estimate in SSc patients the macrovascular function by measuring of the Intima-Media Thickness (IMT) of high-caliber and periferic small-caliber arteries, and to evaluate the possible correlation with microvascular blood perfusion (BP) assessed by Laser Speckle Contrast Analysis (LASCA). Methods: Twenty-nine female SSc patients (mean age 65.7±12.07 SD years, mean disease duration 97.3±68.01 SD months) were enrolled after informed consent. Carotid IMT was evaluated through B-mode US imaging (Esaote, Genoa) using transducer 18 MHz on both right and left common carotid arteries (CCA) as well as ulnar (UA) and radial arteries (RadA). Therefore, an average IMT score was obtained for any evaluated site. Peripheral BP was assessed by LASCA (Perimed-Sweden) at the level of fingertips, periungueal areas, dorsum and palm of both hands, and face. The BP values were reported as perfusion units (PU) (2). In addition nailfold videocapillaroscopy (NVC) in order to assess the microvascular morphological status was done by nailfold video capillaroscopy (NVC) considering the different progressive SSc patterns and the microangiopathy evolution score (MES) (3–4). Results: A positive correlation was observed between CCA IMT and age (p=0.004) and disease duration (p=0.02). On the other hand, no significant correlations were observed between IMT of periferic small-caliber arteries (UA and RadA) and age or disease duration. Positive correlations were found between microvascular damage, as assessed by MES and IMT at the level of periferic small-caliber arteries.No significant correlation was observed between macrovascular involvement of high-caliber arteries and peripheral BP as assessed by LASCA. However, at the peripheral site a correlation was observed between RadA IMT and palm (p=0.05), periungueal (p=0.04) and dorsum of hand BP (p=0.0006), as assessed by LASCA. UA IMT showed a correlation limited to the dorsum of the hand (p=0.003). Conclusions: Significant correlations seem to exist between increased IMT of periferic small-caliber arteries (macrocirculation) and altered peripheral BP (LASCA) at the level of hand microvessels (microcirculation) in SSc patients. These results were found strength by a further correlation with the microvascular damage (MES). References: Hettema Me et al. Rheumatology (Oxford) 2008;47:578–83. Ruaro B et al. Ann Rheum Dis 2014;73:1181–5. Sulli A, et al. Ann Rheum Dis 2008;67:885–7. Cutolo et al. J Rheumatol 2000; 27;155.60. Disclosure of Interest: None declared